Ultra-high strength metal powder cored flux-cored welding wire and preparation method thereof
By using specific components and the preparation method of modified titanium dioxide in welding wire, the existing ultra-high strength metal powder-core flux core welding wire has been solved, and the wire feeding rate, pore inclusion and insufficient strength during welding process is achieved, and high Welding parts with good density and uniformity and efficient welding process.
Patent Information
- Application Number
- CN202411764269.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing ultra-high strength metal powder-core flux-core welding wires have low wire feeding rate during welding, easy to cause pore inclusions at the welding, and poor composition and structure uniformity, resulting in low strength.
The core of the components including carbon, silicon, manganese, nickel, molybdenum, chromium, copper, boron, titanium, magnesium, aluminum, calcium silicate, strontium carbonate, lanthanum carbonate, sodium fluoride and modified titanium dioxide are modified by The preparation method of titanium dioxide and the densification treatment of the flux core components can improve the flowability and reaction rate of the welding system, and enhance the crack resistance and strength of the welded parts.
It improves the density of welding wire and the uniformity between components, enhances the crack resistance and strength of the welded parts, reduces pores and inclusion rates, and improves the wire feeding rate and welding quality during welding.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding materials, and in particular to an ultra-high strength metal powder cored flux-cored welding wire and a preparation method thereof. Background Art
[0002] Although modern welding materials have made great progress in operating process performance and welding efficiency, there are still many problems to be solved in the field of ultra-high strength welding materials, especially ultra-high strength metal powder cored flux-cored welding wire, which is a mountain to be conquered in the field of welding materials.
[0003] Although there are many technical documents that disclose various high-strength flux-cored welding wires, for example, CN104903046B discloses a high-strength flux-cored welding wire, which, based on the overall weight of the welding wire, includes: carbon (C): 0.03~0.12%, silicon (Si): 0.3~1.4%, manganese (Mn): 1.5~3.5%, nickel (Ni): 2.5~3.5%, molybdenum (Mo): 0.3~1.0%, chromium (Cr): 0.3~1.0%, copper (Cu): 0.4~1.0%, boron (B): 0.001~0.020%, titanium (Ti) + magnesium (Mg): 0.02~1.5%, the rest is Fe and other impurities, and includes: TiO 2 : 4.5~9.0%, SiO 2 and ZrO 2 One or two of: 0.2~2.0%, CaCO 3 :0.1~1.0%,one or more of K, Na, Li alkali metal oxides: 0.10~1.5%,F (F) Alkali and alkaline earth metal fluoride compounds with a content of 0.025~0.5%. However, in the actual welding process, the wire feeding rate of flux-cored wire is lower than that of solid wire, pores are easily included in the weld, and the uniformity of the composition and organization of the weld is poor, resulting in low strength. Problems still exist. Summary of the invention
[0004] To this end, the present invention provides an ultra-high strength metal powder cored flux-cored welding wire and a preparation method thereof to solve the above-mentioned problems in the prior art.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] According to a first aspect of the present invention, an ultra-high strength metal powder cored flux-cored welding wire comprises a steel strip and a flux core, wherein the flux core is filled inside the steel strip, and based on the overall weight of the welding wire, the flux core comprises: carbon: 0.03-0.10%, silicon: 0.3-1.0%, manganese: 1.0-3.0%, nickel: 2.6-3.0%, molybdenum: 0.5-1.0%, chromium: 0.3-1.0%, copper: 0.1-0.4%, boron: 0.001-0.020%, titanium: 0.03-0.07%, magnesium: 0.05-1.0%, aluminum: 0.3-0.6%, calcium silicate: 1.2-3.0%, strontium carbonate: 0.3-0.8%, lanthanum carbonate 0.3-0.8%, sodium fluoride 0.5-1.5%, modified titanium dioxide: 0.08-1.0%, and the rest is Fe and other impurities.
[0007] Modified titanium dioxide, calcium silicate, strontium carbonate, lanthanum carbonate, etc. are slag-forming materials. They are decomposed into silicon dioxide, calcium oxide, strontium oxide and lanthanum oxide during the welding process. They are highly active and have low melting point substances generated, which improves the fluidity of the flux system and provides a basis for the full occurrence of solid phase reaction. At the same time, due to the presence of Al, part of silicon dioxide, calcium oxide, strontium oxide and lanthanum oxide will be reduced. The reduced strontium and lanthanum atoms enter the weld, which can improve the crack resistance of the welded parts, refine the welded grains, change the microstructure, and thus improve the welding strength. The role of sodium fluoride in the welding process is mainly reflected in improving welding quality, reducing welding temperature, and reducing welding deformation and cracks.
[0008] Furthermore, the mass of the flux core filled in the steel strip is 18-30% of the total mass of the welding wire.
[0009] Furthermore, the steel strip is a stainless steel strip.
[0010] Furthermore, the density of the flux-cored welding wire is 7.9-8.1 g / cm 3 .
[0011] Furthermore, the preparation method of the modified titanium dioxide comprises:
[0012] Step (a): preparing a glucose solution with a concentration of 10-20%, adding 5-10% sodium citrate to obtain a base solution;
[0013] Step (b): adding titanium dioxide powder to the base liquid at a mass ratio of 1:0.3-0.4, and adding 3-5% of a coupling agent, and ball milling for 5-10 hours to obtain a precursor;
[0014] Step (c): the precursor in step (b) is allowed to stand for 1-3 minutes under ammonia conditions, and then dried and dispersed under vacuum conditions to obtain modified titanium dioxide.
[0015] In this scheme, citrate and ammonium radicals are thermally decomposed to form protective gas, and citrate radicals react with metal oxides to generate volatile gases and soluble salts, thereby effectively removing oxides from the welding interface; the presence of titanium dioxide can make the slag of the welding rod have a lower melting point and viscosity, and at the same time, as a slag-forming agent, deoxidizer, diluent and stabilizer, it can reduce the melting point of the welding rod, so that the welding rod can work when a normal current is passed; glucose can show the effect of corrosion inhibitor. In addition to the above effects, the surface of the modified titanium dioxide grafted with citrate ions and attached with a glucose film also plays the following three roles: 1. Improve the bonding strength of the flux core, that is, the density. Glucose can improve the overall density as a binder in the subsequent preparation process; 2. Increase the reaction rate of the flux and the wire feeding rate; 3. Reduce pores and inclusion rate. The citric acid-modified titanium dioxide reduces the melting temperature and reduces the surface tension of the melt, making it easy to fill. In addition, the direct part is ammonium citrate, which provides a nitrogen source for the titanium in the core component during welding, promotes the formation of titanium nitride, aluminum nitride and other substances, can inhibit grain growth, and improve welding performance. Since excessive nitrogen entering the weldment will cause performance degradation, it is necessary to control the treatment time of the ammonia atmosphere, thereby controlling the nitrogen content in the core composition. In addition, when glucose and citric acid decompose, the incompletely reacted carbon will enter the weldment.
[0016] Furthermore, the coupling agent is tetrabutyl titanate or a silane coupling agent.
[0017] Furthermore, in step (c), the drying temperature is 60-80°C.
[0018] The present invention also provides a method for preparing an ultra-high strength metal powder cored flux-cored welding wire, comprising the following steps:
[0019] (1) Pre-treatment of the core material: weigh the core components in proportion, mix them evenly, and dry them in low temperature vacuum to obtain a mixed material;
[0020] (2) Densification of the core components: Place the mixture obtained in step (1) in a dry ball mill and ball mill for 1-3 hours under nitrogen protection to obtain a dense material;
[0021] (3) Forming: adding the uniformly mixed flux core obtained in step (2) into the U-shaped groove for preparing the steel strip, and then closing, reducing, drawing and winding the U-shaped groove to obtain an ultra-high strength metal powder core type flux-cored welding wire.
[0022] The densification process in step (2) is mainly to make the components of the core evenly dispersed, while refining the particles of each component and ensuring that the particles of each component are in full contact with each other.
[0023] Furthermore, the low-temperature drying temperature in step (1) is 50-70° C., and the heat preservation time is 120 minutes.
[0024] Furthermore, in step (2), the average particle size of the dense material is 5-10 μm.
[0025] Compared with the existing technology, this solution has the following advantages:
[0026] The core density is high, the components are evenly dispersed, and the weld consistency is good;
[0027] The components of the flux core are fully matched, the molten material has good fluidity and filling during welding, few pores, high flux reaction rate and high wire feeding rate.
[0028] The obtained welded parts have high crack resistance, good grain uniformity and high welding strength. DETAILED DESCRIPTION
[0029] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0030] An ultra-high strength metal powder core type flux-cored welding wire, comprising a stainless steel strip and a flux core, wherein the flux core is filled inside the steel strip, and the filling amount is 25% of the total mass of the welding wire. Based on the overall weight of the welding wire, the flux core comprises: carbon: 0.08%, silicon: 0.5%, manganese: 1.5%, nickel: 2.8%, molybdenum: 0.8%, chromium: 0.6%, copper: 0.2%, boron: 0.01%, titanium: 0.04%, magnesium: 0.2%, aluminum: 0.5%, calcium silicate: 1.8%, strontium carbonate: 0.5%, lanthanum carbonate: 0.5%, sodium fluoride: 0.5%, modified titanium dioxide: 0.5%, and the rest is Fe and other impurities;
[0031] The density of flux-cored wire is 8.0g / cm 3 ;
[0032] The preparation method of modified titanium dioxide comprises:
[0033] Step (a): preparing a 15% glucose solution, adding 8% sodium citrate to obtain a base solution;
[0034] Step (b): adding titanium dioxide powder to the base liquid at a mass ratio of 1:0.3, and adding 4% of a coupling agent, and ball milling for 8 hours to obtain a precursor;
[0035] Step (c): the precursor in step (b) is allowed to stand for 2 minutes under ammonia conditions, and then dried and dispersed at 70° C. under vacuum conditions to obtain modified titanium dioxide;
[0036] The method for preparing the ultra-high strength metal powder cored flux-cored welding wire comprises the following steps:
[0037] (1) Pretreatment of the core material: weigh the core components in proportion and mix them evenly, and dry them under low temperature vacuum at 60° C. for 120 min to obtain a mixed material;
[0038] (2) Densification of the core component: The mixed material obtained in step (1) is placed in a dry ball mill and ball milled for 2 h under nitrogen protection to obtain a dense material with an average particle size of 7 μm;
[0039] (3) Forming: adding the uniformly mixed flux core obtained in step (2) into the U-shaped groove for preparing the steel strip, and then closing, reducing, drawing and winding the U-shaped groove to obtain an ultra-high strength metal powder core type flux-cored welding wire with a diameter of 1.00 mm. Example 2
[0040] An ultra-high strength metal powder core type flux-cored welding wire, comprising a stainless steel strip and a flux core, wherein the flux core is filled inside the steel strip, and the filling amount is 20% of the total mass of the welding wire. Based on the overall weight of the welding wire, the flux core comprises: carbon: 0.08%, silicon: 0.5%, manganese: 1.5%, nickel: 2.8%, molybdenum: 0.8%, chromium: 0.6%, copper: 0.2%, boron: 0.01%, titanium: 0.04%, magnesium: 0.2%, aluminum: 0.5%, calcium silicate: 1.8%, strontium carbonate: 0.5%, lanthanum carbonate: 0.5%, sodium fluoride: 0.5%, modified titanium dioxide: 0.5%, and the rest is Fe and other impurities;
[0041] The density of flux-cored wire is 7.9g / cm 3 ;
[0042] The preparation method of modified titanium dioxide comprises:
[0043] Step (a): preparing a 15% glucose solution, adding 8% sodium citrate to obtain a base solution;
[0044] Step (b): adding titanium dioxide powder to the base liquid at a mass ratio of 1:0.3, and adding 4% of a coupling agent, and ball milling for 8 hours to obtain a precursor;
[0045] Step (c): the precursor in step (b) is allowed to stand for 2 minutes under ammonia conditions, and then dried and dispersed at 70° C. under vacuum conditions to obtain modified titanium dioxide;
[0046] The method for preparing the ultra-high strength metal powder cored flux-cored welding wire comprises the following steps:
[0047] (1) Pretreatment of the core material: weigh the core components in proportion and mix them evenly, and dry them under low temperature vacuum at 60° C. for 120 min to obtain a mixed material;
[0048] (2) Densification of the core component: The mixed material obtained in step (1) is placed in a dry ball mill and ball milled for 2 h under nitrogen protection to obtain a dense material with an average particle size of 7 μm;
[0049] (3) Forming: adding the uniformly mixed flux core obtained in step (2) into the U-shaped groove for preparing the steel strip, and then closing, reducing, drawing and winding the U-shaped groove to obtain an ultra-high strength metal powder core type flux-cored welding wire with a diameter of 1.00 mm. Example 3
[0050] An ultra-high strength metal powder core type flux-cored welding wire, comprising a stainless steel strip and a flux core, wherein the flux core is filled inside the steel strip, and the filling amount is 25% of the total mass of the welding wire. Based on the overall weight of the welding wire, the flux core comprises: carbon: 0.05%, silicon: 0.8%, manganese: 2.0%, nickel: 2.9%, molybdenum: 0.8%, chromium: 0.6%, copper: 0.2%, boron: 0.008%, titanium: 0.04%, magnesium: 0.2%, aluminum: 0.6%, calcium silicate: 2.0%, strontium carbonate: 0.5%, lanthanum carbonate: 0.8%, sodium fluoride 1.0%, modified titanium dioxide: 0.8%, and the rest is Fe and other impurities;
[0051] The density of flux-cored wire is 8.0g / cm 3 ;
[0052] The preparation method of modified titanium dioxide comprises:
[0053] Step (a): preparing a 15% glucose solution, adding 8% sodium citrate to obtain a base solution;
[0054] Step (b): adding titanium dioxide powder to the base liquid at a mass ratio of 1:0.4, and adding 4% of a coupling agent, and ball milling for 8 hours to obtain a precursor;
[0055] Step (c): the precursor in step (b) is allowed to stand for 2 minutes under ammonia conditions, and then dried and dispersed at 70° C. under vacuum conditions to obtain modified titanium dioxide;
[0056] The method for preparing the ultra-high strength metal powder cored flux-cored welding wire comprises the following steps:
[0057] (1) Pretreatment of the core material: weigh the core components in proportion and mix them evenly, and dry them under low temperature vacuum at 60° C. for 120 min to obtain a mixed material;
[0058] (2) Densification of the core component: The mixed material obtained in step (1) is placed in a dry ball mill and ball milled for 2 h under nitrogen protection to obtain a dense material with an average particle size of 7 μm;
[0059] (3) Forming: adding the uniformly mixed flux core obtained in step (2) into the U-shaped groove for preparing the steel strip, and then closing, reducing, drawing and winding the U-shaped groove to obtain an ultra-high strength metal powder core type flux-cored welding wire with a diameter of 1.00 mm. Comparative Example 1
[0060] An ultra-high strength metal powder core type flux-cored welding wire, comprising a stainless steel strip and a flux core, wherein the flux core is filled inside the steel strip, and the filling amount is 30% of the total mass of the welding wire. Based on the overall weight of the welding wire, the flux core comprises: carbon: 0.08%, silicon: 0.5%, manganese: 1.5%, nickel: 2.8%, molybdenum: 0.8%, chromium: 0.6%, copper: 0.2%, boron: 0.01%, titanium: 0.04%, magnesium: 0.2%, aluminum: 0.5%, calcium silicate: 1.8%, strontium carbonate: 0.5%, lanthanum carbonate: 0.5%, sodium fluoride: 0.5%, modified titanium dioxide: 0.5%, and the rest is Fe and other impurities;
[0061] The density of flux-cored wire is 8.0g / cm 3 ;
[0062] The preparation method of modified titanium dioxide comprises:
[0063] Step (a): preparing a 15% glucose solution, adding 8% sodium citrate to obtain a base solution;
[0064] Step (b): adding titanium dioxide powder to the base liquid at a mass ratio of 1:0.3, and adding 4% of a coupling agent, and ball milling for 8 hours to obtain a precursor;
[0065] Step (c): the precursor in step (b) is allowed to stand for 2 minutes under ammonia conditions, and then dried and dispersed at 70° C. under vacuum conditions to obtain modified titanium dioxide;
[0066] The method for preparing the ultra-high strength metal powder cored flux-cored welding wire comprises the following steps:
[0067] (1) Pretreatment of the core material: weigh the core components in proportion and mix them evenly, and dry them under low temperature vacuum at 60° C. for 120 min to obtain a mixed material;
[0068] (2) Densification of the core component: The mixed material obtained in step (1) is placed in a dry ball mill and ball milled for 2 h under nitrogen protection to obtain a dense material with an average particle size of 7 μm;
[0069] (3) Forming: adding the uniformly mixed flux core obtained in step (2) into the U-shaped groove for preparing the steel strip, and then closing, reducing, drawing and winding the U-shaped groove to obtain an ultra-high strength metal powder core type flux-cored welding wire with a diameter of 1.00 mm. Comparative Example 2
[0070] An ultra-high strength metal powder core type flux-cored welding wire, comprising a stainless steel strip and a flux core, wherein the flux core is filled inside the steel strip, and the filling amount is 25% of the total mass of the welding wire. Based on the overall weight of the welding wire, the flux core comprises: carbon: 0.08%, silicon: 0.5%, manganese: 1.5%, nickel: 2.8%, molybdenum: 0.8%, chromium: 0.6%, copper: 0.2%, boron: 0.01%, titanium: 0.04%, magnesium: 0.2%, aluminum: 0.5%, calcium silicate: 1.8%, strontium carbonate: 0.5%, lanthanum carbonate: 0.5%, sodium fluoride: 0.5%, modified titanium dioxide: 0.5%, and the rest is Fe and other impurities;
[0071] The density of flux-cored wire is 7.7g / cm 3 ;
[0072] The preparation method of modified titanium dioxide comprises:
[0073] Step (a): preparing a 15% glucose solution, adding 8% sodium citrate to obtain a base solution;
[0074] Step (b): adding titanium dioxide powder to the base liquid at a mass ratio of 1:0.3, and adding 4% of a coupling agent, and ball milling for 8 hours to obtain a precursor;
[0075] Step (c): the precursor in step (b) is allowed to stand for 2 minutes under ammonia conditions, and then dried and dispersed at 70° C. under vacuum conditions to obtain modified titanium dioxide;
[0076] The method for preparing the ultra-high strength metal powder cored flux-cored welding wire comprises the following steps:
[0077] (1) Pretreatment of the core material: weigh the core components in proportion and mix them evenly, and dry them under low temperature vacuum at 60° C. for 120 min to obtain a mixed material;
[0078] (2) Densification of the core component: The mixed material obtained in step (1) is placed in a dry ball mill and ball milled for 2 h under nitrogen protection to obtain a dense material with an average particle size of 7 μm;
[0079] (3) Forming: adding the uniformly mixed flux core obtained in step (2) into the U-shaped groove for preparing the steel strip, and then closing, reducing, drawing and winding the U-shaped groove to obtain an ultra-high strength metal powder core type flux-cored welding wire with a diameter of 1.00 mm. Comparative Example 3
[0080] An ultra-high strength metal powder core type flux-cored welding wire, comprising a stainless steel strip and a flux core, wherein the flux core is filled inside the steel strip, and the filling amount is 25% of the total mass of the welding wire. Based on the overall weight of the welding wire, the flux core comprises: carbon: 0.08%, silicon: 0.5%, manganese: 1.5%, nickel: 2.8%, molybdenum: 0.8%, chromium: 0.6%, copper: 0.2%, boron: 0.01%, titanium: 0.04%, magnesium: 0.2%, aluminum: 0.5%, sodium fluoride 0.5%, and the rest is Fe and other impurities;
[0081] The density of flux-cored wire is 8.0g / cm 3 ;
[0082] The method for preparing the ultra-high strength metal powder cored flux-cored welding wire comprises the following steps:
[0083] (1) Pretreatment of the core material: weigh the core components in proportion and mix them evenly, and dry them under low temperature vacuum at 60° C. for 120 min to obtain a mixed material;
[0084] (2) Densification of the core component: The mixed material obtained in step (1) is placed in a dry ball mill and ball milled for 2 h under nitrogen protection to obtain a dense material with an average particle size of 7 μm;
[0085] (3) Forming: adding the uniformly mixed flux core obtained in step (2) into the U-shaped groove for preparing the steel strip, and then closing, reducing, drawing and winding the U-shaped groove to obtain an ultra-high strength metal powder core type flux-cored welding wire with a diameter of 1.00 mm. Comparative Example 4
[0086] An ultra-high strength metal powder core type flux-cored welding wire, comprising a stainless steel strip and a flux core, wherein the flux core is filled inside the steel strip, and the filling amount is 25% of the total mass of the welding wire. Based on the overall weight of the welding wire, the flux core comprises: carbon: 0.08%, silicon: 0.5%, manganese: 1.5%, nickel: 2.8%, molybdenum: 0.8%, chromium: 0.6%, copper: 0.2%, boron: 0.01%, titanium: 0.04%, magnesium: 0.2%, aluminum: 0.5%, calcium silicate: 1.8%, strontium carbonate: 0.5%, lanthanum carbonate: 0.5%, sodium fluoride: 0.5%, modified titanium dioxide: 0.5%, and the rest is Fe and other impurities;
[0087] The density of flux-cored wire is 8.0g / cm 3 ;
[0088] The preparation method of modified titanium dioxide comprises:
[0089] Step (a): preparing a 15% glucose solution, adding 8% sodium citrate to obtain a base solution;
[0090] Step (b): adding titanium dioxide powder to the base liquid at a mass ratio of 1:0.3, and adding 4% of a coupling agent, and ball milling for 8 hours to obtain a precursor;
[0091] Step (c): the precursor in step (b) is allowed to stand for 5 minutes under ammonia conditions, and then dried and dispersed at 70° C. under vacuum conditions to obtain modified titanium dioxide;
[0092] The method for preparing the ultra-high strength metal powder cored flux-cored welding wire comprises the following steps:
[0093] (1) Pretreatment of the core material: weigh the core components in proportion and mix them evenly, and dry them under low temperature vacuum at 60° C. for 120 min to obtain a mixed material;
[0094] (2) Densification of the core component: The mixed material obtained in step (1) is placed in a dry ball mill and ball milled for 2 h under nitrogen protection to obtain a dense material with an average particle size of 7 μm;
[0095] (3) Forming: adding the uniformly mixed flux core obtained in step (2) into the U-shaped groove for preparing the steel strip, and then closing, reducing, drawing and winding the U-shaped groove to obtain an ultra-high strength metal powder core type flux-cored welding wire with a diameter of 1.00 mm. Comparative Example 5
[0096] An ultra-high strength metal powder core type flux-cored welding wire, comprising a stainless steel strip and a flux core, wherein the flux core is filled inside the steel strip, and the filling amount is 25% of the total mass of the welding wire. Based on the overall weight of the welding wire, the flux core comprises: carbon: 0.08%, silicon: 0.5%, manganese: 1.5%, nickel: 2.8%, molybdenum: 0.8%, chromium: 0.6%, copper: 0.2%, boron: 0.01%, titanium: 0.04%, magnesium: 0.2%, aluminum: 0.5%, calcium silicate: 1.8%, strontium carbonate: 0.5%, lanthanum carbonate: 0.5%, sodium fluoride: 0.5%, modified titanium dioxide: 0.5%, and the rest is Fe and other impurities;
[0097] The density of flux-cored wire is 8.0g / cm 3 ;
[0098] The preparation method of modified titanium dioxide comprises:
[0099] Step (a): preparing a 15% glucose solution, adding 8% sodium citrate to obtain a base solution;
[0100] Step (b): adding titanium dioxide powder to the base liquid at a mass ratio of 1:0.3, and adding 4% of a coupling agent, and ball milling for 8 hours to obtain a precursor;
[0101] Step (c): drying and dispersing the precursor in step (b) at 70° C. under vacuum conditions to obtain modified titanium dioxide;
[0102] The method for preparing the ultra-high strength metal powder cored flux-cored welding wire comprises the following steps:
[0103] (1) Pretreatment of the core material: weigh the core components in proportion and mix them evenly, and dry them under low temperature vacuum at 60° C. for 120 min to obtain a mixed material;
[0104] (2) Densification of the core component: The mixed material obtained in step (1) is placed in a dry ball mill and ball milled for 2 h under nitrogen protection to obtain a dense material with an average particle size of 7 μm;
[0105] (3) Forming: adding the uniformly mixed flux core obtained in step (2) into the U-shaped groove for preparing the steel strip, and then closing, reducing, drawing and winding the U-shaped groove to obtain an ultra-high strength metal powder core type flux-cored welding wire with a diameter of 1.00 mm. Comparative Example 6
[0106] An ultra-high strength metal powder core type flux-cored welding wire, comprising a stainless steel strip and a flux core, wherein the flux core is filled inside the steel strip, and the filling amount is 25% of the total mass of the welding wire. Based on the overall weight of the welding wire, the flux core comprises: carbon: 0.08%, silicon: 0.5%, manganese: 1.5%, nickel: 2.8%, molybdenum: 0.8%, chromium: 0.6%, copper: 0.2%, boron: 0.01%, titanium: 0.04%, magnesium: 0.2%, aluminum: 0.5%, calcium silicate: 1.8%, strontium carbonate: 0.5%, lanthanum carbonate: 0.5%, sodium fluoride: 0.5%, modified titanium dioxide: 0.5%, and the rest is Fe and other impurities;
[0107] The density of flux-cored wire is 8.0g / cm 3 ;
[0108] The preparation method of modified titanium dioxide comprises:
[0109] Step (a): preparing a 15% glucose solution, adding 8% sodium citrate to obtain a base solution;
[0110] Step (b): adding titanium dioxide powder to the base liquid at a mass ratio of 1:0.3, and adding 4% of a coupling agent, and ball milling for 8 hours to obtain a precursor;
[0111] Step (c): the precursor in step (b) is allowed to stand for 2 minutes under ammonia conditions, and then dried and dispersed at 70° C. under vacuum conditions to obtain modified titanium dioxide;
[0112] The method for preparing the ultra-high strength metal powder cored flux-cored welding wire comprises the following steps:
[0113] (1) Pretreatment of the core material: weigh the core components in proportion and mix them evenly, and dry them under low temperature vacuum at 60° C. for 120 min to obtain a mixed material;
[0114] (2) Forming: adding the uniformly mixed flux core obtained in step (1) into the U-shaped groove for preparing the steel strip, and then closing, reducing, drawing and winding the U-shaped groove to obtain an ultra-high strength metal powder core type flux-cored welding wire with a diameter of 1.00 mm.
[0115] The welding process is: voltage 26V; current 240A; wire feeding speed: 420 / min; gas flow rate: 25L / min; the distance the welding wire extends out of the conductive nozzle: 25mm.
[0116] The welding effect of the above process and the mechanical properties of the deposited metal are shown in Table 1.
[0117] Table 1
[0118]
[0119] Compared with comparative examples 1-6, embodiments 1-3 have good welding effects, small spatters, beautiful weld shapes, and no surface cracks.
[0120] It can be seen from Comparative Example 1 that there are many welding defects in the welded parts, which may be caused by the wire feeding speed being too fast. The higher the wire feeding speed, the faster the gas in the molten pool can escape to prevent the formation of pores. Under the above welding process, the filling amount of Comparative Example 1 is high. Under the same wire feeding speed conditions as Example 1, the weld width and excess height of Comparative Example 1 increase, while the weld thickness and penetration depth decrease, resulting in insufficient time for the gas in the molten pool to escape, forming pores, and more welding spatter. Defects such as pores cause a decrease in mechanical properties.
[0121] It can be seen from Comparative Example 2 that the presence of pores results in lower mechanical properties than Example 1. The presence of pores is due to the lower density of Comparative Example 2 relative to Example 1, that is, there is more air in the core, which requires a longer time for the air to escape. Therefore, at the same wire feeding speed, Comparative Example 2 has more pores than Example 1.
[0122] The welded parts of Comparative Example 3 have more welding defects, which is due to the lack of addition of calcium silicate, strontium carbonate, lanthanum carbonate, and modified titanium dioxide. These components are crucial for improving the fluidity of the flux core after melting, floating welding slag, etc., and can refine the grains of the welding part and improve the welding strength. Compared with Example 1, Comparative Example 3 has poor welding effect, more spatter, poor weld formation, surface cracks and pores at the same wire feeding speed, so the performance is poor.
[0123] Comparative Examples 4 and 5 are mainly about the effect of nitrogen on the flux. Compared with Example 1, Comparative Example 4 has excessive nitrogen, which leads to the formation of nitrogen pores and excessive nitrides, which reduces the bonding strength between grains and forms microcracks. Compared with Example 1, Comparative Example 5 has too little nitrogen, which makes the amount of titanium nitride and other substances less, and the grain refinement effect becomes poor.
[0124] Comparative Example 6 was not densified during preparation, so the mixing uniformity of its core components was poor, resulting in much spatter and the presence of pores. In addition, due to the poor uniformity of the weld structure, microcracks were formed, which ultimately manifested as a reduction in mechanical properties.
Claims
1. An ultra-high strength metal powder cored flux-cored welding wire, characterized in that: It comprises a steel strip and a flux core, wherein the flux core is filled inside the steel strip. Based on the overall weight of the welding wire, the flux core comprises: carbon: 0.03-0.10%, silicon: 0.3-1.0%, manganese: 1.0-3.0%, nickel: 2.6-3.0%, molybdenum: 0.5-1.0%, chromium: 0.3-1.0%, copper: 0.1-0.4%, boron: 0.001-0.020%, titanium: 0.03-0.07%, magnesium: 0.05-1.0%, aluminum: 0.3-0.6%, calcium silicate: 1.2-3.0%, strontium carbonate: 0.3-0.8%, lanthanum carbonate 0.3-0.8%, sodium fluoride 0.5-1.5%, modified titanium dioxide: 0.08-1.0%, and the rest is Fe and other impurities; The preparation method of the modified titanium dioxide comprises: Step (a): preparing a glucose solution with a concentration of 10-20%, adding 5-10% sodium citrate to obtain a base solution; Step (b): adding 30%-40% of the mass of titanium dioxide powder to the base liquid, and adding 3-5% of a coupling agent, and ball milling for 5-10 hours to obtain a precursor; the coupling agent is tetrabutyl titanate or a silane coupling agent; Step (c): the precursor in step (b) is allowed to stand for 1-3 minutes under ammonia conditions, and then dried and dispersed under vacuum conditions to obtain modified titanium dioxide; The mass of the flux core filled in the steel strip is 18-25% of the total mass of the welding wire; The density of the flux-cored wire is 7.9-8.1 g / cm 3 .
2. The ultra-high strength metal powder cored flux-cored welding wire according to claim 1, characterized in that: The steel belt is a stainless steel belt.
3. The ultra-high strength metal powder cored flux-cored welding wire according to claim 1, characterized in that: In step (c), the temperature for drying and dispersing under vacuum conditions is 70°C.
4. The method for preparing the ultra-high strength metal powder cored flux-cored welding wire according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Pre-treatment of the core material: weigh the core components in proportion, mix them evenly, and dry them in low temperature vacuum to obtain a mixed material; (2) Densification of the core components: Place the mixture obtained in step (1) in a dry ball mill and ball mill for 1-3 hours under nitrogen protection to obtain a dense material; (3) Forming: adding the uniformly mixed flux core obtained in step (2) into the U-shaped groove for preparing the steel strip, and then closing, reducing, drawing and winding the U-shaped groove to obtain an ultra-high strength metal powder core type flux-cored welding wire.
5. The method for preparing the ultra-high strength metal powder cored flux-cored welding wire according to claim 4, characterized in that: The low-temperature vacuum drying temperature of step (1) is 50-70° C., and the heat preservation time is 120 minutes.
6. The method for preparing the ultra-high strength metal powder cored flux-cored welding wire according to claim 4, characterized in that: In step (2), the average particle size of the dense material is 5-10 μm.
Citation Information
Patent Citations
Ultra-high-strength flux-cored wire arc welding joint and welding wire for manufacturing the welding joint
CN104903046B
Seamless flux-cored wire for welding high-strength steel
CN113996971A
Aluminum metal core welding wire forming process
CN116372422A